English Teachers’ Readiness to Implementing Online Learning - Ni Wayan Pitriani; Nyoman Karina Wedhanti (Indonesian Journal Of Educational Research and Review, 2021)
Nowadays, education system is conducted in the different ways in which the learning and teaching process can be done as a distance learning without time and space limitation or commonly known as online learning. This study aimed at analyzing teachers’ readiness implementing online learning and to know strengths and weakness of online learning. This study was formed in descriptive qualitative research. Five teachers and a principal involved as subject meanwhile object of the study was teachers’ readiness implementing online learning. The data were gained through observation, survey, and interview by the use of observation check-list, questionnaire, and interview guide. The obtained data were analyzed by using Qualitative Data Analysis. The result showed the readiness of English teachers implementing online learning was good enough. Teachers was ready in 3 procedures like opening/pre-activity, main activity, and post-activity that conducted by the online meeting. Unstable of internet and not optimal learning were the disadvantages of online learning because teachers couldn't meet students directly and teacher only could transfer knowledge or theory and teacher couldn't educate students’ character. While for advantages aspect, teacher easier and simpler in teaching because they could teach anywhere. Online learning program was supportive and helpful to the institution, especially the school in this abnormal situation and condition.